Study on Swirling Flow and Spray Characteristics of Central Stage Direct Injection Combustor - Wenjie Jiang; Ziyu Qi; Jinhu Yang; Deqing Mei; Kaixing Wang; Yushuai Liu; Shaolin Wang; Fuqiang Liu; Yong Mu; Cunxi Liu; Gang Xu (Energies)
To investigate the physical phenomena interactions between airstream and liquid injection or droplets within a complex multi-stage swirl flow field, this study investigated the flow field and spray characteristics in a central stage direct injection combustor with a variety of optical diagnostic techniques, including using time-resolved particle image velocimetry (PIV) to measure the swirl flow field, using time-resolved planar Mie scattering (PMie) to measure the spray pattern, and using a laser particle size analyzer (LPSA) to measure the spray droplet size and its distribution. The results indicate that the lip recirculation zone (LRZ) and the swirl jet zone (SJZ) significantly influence droplet spatial and size distribution characteristics, such as spray penetration, cone angle, and droplet size. Due to the unique characteristics of the dual-stage swirl atomizer, the spray cone angle and penetration do not increase monotonically with the gas Weber number (<semantics>Weg</semantics>). For the pilot stage, at a constant <semantics>Weg</semantics>, both the spray cone angle and penetration increase with higher fuel injection velocity. At different fuel injection velocities, the spray penetration increases with rising <semantics>Weg</semantics>. When the fuel injection velocity is low, the cone angle initially increases and then decreases as <semantics>Weg</semantics> grows. The results about the effect of <semantics>Weg</semantics> on droplet size distribution further support this conclusion. The Sauter mean diameter (SMD) of the main and pilot stage decreases with increasing relative pressure drop of air until reaching a stable state. The aerodynamic shear of the swirling airstream is sufficient to promote thorough fuel atomization, ensuring that the SMD remains low at the whole operating condition. Therefore, for the dual-stage swirl atomizer investigated in this study, good atomization can be achieved under low operating conditions, which provides a theoretical foundation and data support for the improvement and design of a low-emission, high-performance atomizer.